2021
DOI: 10.37398/jsr.2021.650507
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of CA-125, Estradiol and Cortisol as Prominent Markers to Diagnose Various Stages of Endometriosis

Abstract: Endometriosis is a chronic inflammatory disease condition that affects an estimated 176 million women worldwide. The disease causes unbearable symptoms of pelvic pain and infertility that limits the quality of reproductive life of affected women. An attempt has been made to identify certain physiological and hormonal factors that may behave as reliable diagnostic markers to assess the various stages of endometriosis. It is a retrospective population-based study. Here a questionnaire-based study was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This is in agreement with another study which found no significant differences in serum levels of oestradiol and progesterone in EMS 24 . Oestradiol has been shown to increase with EMS progression 25 , but levels did not differ in EMS compared to controls 26 . Interestingly, when we have looked at the oestradiol to progesterone ratio, there was a significant increase in the EMS group.…”
Section: Discussionmentioning
confidence: 85%
“…This is in agreement with another study which found no significant differences in serum levels of oestradiol and progesterone in EMS 24 . Oestradiol has been shown to increase with EMS progression 25 , but levels did not differ in EMS compared to controls 26 . Interestingly, when we have looked at the oestradiol to progesterone ratio, there was a significant increase in the EMS group.…”
Section: Discussionmentioning
confidence: 85%